PENGARUH PENYERAPAN TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI SUMATERA BARAT - Maulia Usni (Jurnal Bisnis Tani, 2022)
An increase in the productivity of the agricultural sector can occur in a region if the number of inhabitants continues to grow. This is based on Karl Marx's theory in Alma (2019) that population growth can increase productivity by using labor as a manager of existing resources in the area, especially agriculture, to meet the food needs of the community. This can be achieved with government support through government policies. West Sumatra Province is one of the provinces that has increased the regional budget for the agricultural sector by up to 10%. Increasing the allocation of the West Sumatra Provincial Budget from 2.86% to 10% will increase the productivity of the agricultural sector through the introduction of agricultural labor. This study uses quantitative analysis with the VECM method in analyzing time series data for a period of 34 years. Research has found that employment negatively affects economic growth Researchers provide advice so that the government and agricultural sector partners can provide training and guidance on the development of professional human resources in their fields.